Enantioselective Synthesis of Axially Chiral Tetrasubstituted Allenes via Lipase-Catalyzed Desymmetrization - Hammel, Matthias; Deska, Jan (Synthesis, 2012)
Lipase from Pseudomonas fluorescens efficiently catalyzes the transesterification of prochiral tetrasubstituted allenic diols yielding highly enantioenriched axially chiral allenyl monoesters. In combination with subsequent 5-endo-trig cyclizations geminally disubstituted dihydrofurans are accessible in high optical purity.
Keywords: allenes; axial chirality; desymmetrization; biocatalysis; 5-endo-trig cyclization